2018
DOI: 10.21203/rs.1.8/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Premedication with intranasal dexmedetomidine decreases barbiturate requirement in pediatric patients sedated for magnetic resonance imaging: a retrospective study

Abstract: Background: Barbiturates are commonly used in ambulatory sedation of pediatric patients. However, use of barbiturates involve risks of respiratory complications. Dexmedetomidine, a highly selective α2-adrenoceptor agonist, is increasingly used for pediatric sedation. Premedication with intranasal (IN) dexmedetomidine offers a non-invasive and efficient possibility to sedate pediatric patients undergoing magnetic resonance imaging (MRI). Our hypothesis was that dexmedetomidine would reduce barbiturate requireme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Dexmedetomidine decreased the amount of thiopental required to sedate people. 13 Results of a retrospective review stated that in 78.5% of paediatric cases, high doses of dexmedetomidine were successful; for 21.5% of patients, additional drugs were necessary. About 25% of cases had side effects, which went away on their own.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…Dexmedetomidine decreased the amount of thiopental required to sedate people. 13 Results of a retrospective review stated that in 78.5% of paediatric cases, high doses of dexmedetomidine were successful; for 21.5% of patients, additional drugs were necessary. About 25% of cases had side effects, which went away on their own.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…[37,38] Intranasal dexmedetomidine can induce sedation within 30 min in pediatric patients. [2, 5, 6, 9, 11, 12, 14-22, 24, 26-28, 31,35,36,38,39] A recent study reported that intranasal dexmedetomidine 4 μg/kg enabled magnetic resonance imaging (MRI) examination without apnea and hypoxemia in infants; [27] however, 30.7% (16/52) of the patients developed bradycardia (<80% of the baseline heart rate), and 3.8% (2/52) developed hypotension (<80% of the baseline mean arterial pressure). As such, intranasal dexmedetomidine alone can be associated with slow onset time, bradycardia, or hypotension.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%